Spin–orbit coupling is the key to unraveling intriguing features of the halogen bond involving astatine. Issue 4 (8th January 2020) - Rossi, Elisa; De Santis, Matteo; Sorbelli, Diego; Storchi, Loriano; Belpassi, Leonardo; Belanzoni, Paola
Abstract : SOC induced charge accumulation on astatine side in Cl–At weakens the halogen bond through reduction of charge transfer, polar flattening and σ-hole. Abstract : The effect of spin–orbit coupling (SOC) on the halogen bond involving astatine has been investigated using state-of-the-art two- and four-component relativistic calculations. Adducts between Cl–X (X = Cl, Br, I and At) and ammonia have been selected to establish a trend on going down the periodic table. The SOC influence has been explored not only on the geometric and energetic features that can be used to characterize the halogen bond strength but also on the three main contributions to it that are the charge transfer, the "σ-hole" ( i.e. the localized region with a net positive electrostatic potential at the halogen site) and the "polar flattening" (which is related to the effective shape of the halogen site). A surprisingly large increase of the Cl–At dipole moment, due to the inclusion of SOC, has been worked out using four-component CCSD(T) reference calculations, indicating that this bond is significantly more ionic than one may predict. Due to the SOC effect, which induces a peculiar charge accumulation on the At side in the Cl–At dimer, a weakening of the astatine-mediated halogen bond occurs arising from the (i) reduced amount of charge transfer, (ii) decrease of the polar flattening and (iii) lowering of the short-range Coulomb potential. The analysis of the electronic structure of the Cl–At moiety allows for a rationalization of the SOC effects on all the considered features of the halogen bond, including an unprecedented unsymmetrical charge back-donation from Cl–At to ammonia.